2017
DOI: 10.1186/s13071-017-2094-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of Rickettsia spp. in ixodid ticks and rodents in suburban, natural and rural habitats in Slovakia

Abstract: BackgroundNatural foci of tick-borne spotted fever group (SFG) rickettsiae of public health concern have been found in Slovakia, but the role of rodents in their circulation is unclear. Ticks (Ixodes ricinus, Ixodes trianguliceps, Dermacentor marginatus, Dermacentor reticulatus, Haemaphysalis concinna and Haemaphysalis inermis) and tissues of rodents (Apodemus flavicollis, Apodemus sylvaticus, Myodes glareolus, Microtus arvalis, Microtus subterraneus and Micromys minutus) were examined for the presence of SFG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 52 publications
0
39
0
1
Order By: Relevance
“…The three nymphs were collected from European robin (E. rubecula) and blackbird (T. merula), which mainly migrate to Norway from Great Britain and Western Europe [41]. The prevalence, 0.4%, is low compared to studies conducted in Europe, both in questing ticks [45,46] and in ticks collected from birds [3,17]. In Great Britain, a study reported a widespread PLOS ONE distribution of R. helvetica in 4/116 questing I. ricinus [47].…”
Section: Resultsmentioning
confidence: 99%
“…The three nymphs were collected from European robin (E. rubecula) and blackbird (T. merula), which mainly migrate to Norway from Great Britain and Western Europe [41]. The prevalence, 0.4%, is low compared to studies conducted in Europe, both in questing ticks [45,46] and in ticks collected from birds [3,17]. In Great Britain, a study reported a widespread PLOS ONE distribution of R. helvetica in 4/116 questing I. ricinus [47].…”
Section: Resultsmentioning
confidence: 99%
“…These results consolidate previous findings describing the presence of these two Rickettsia species in Ixodes ricinus from the north‐west of Tunisia (Sfar et al, ). Nevertheless, these two species were identified not only in ticks feeding on the common wall lizard from the neighbour country Italy (Tomassone et al, ) but also in rodents blood and infesting fleas and mites from Lithuania (Busaitiene et al, ; Radzijevskaja et al, ) and Slovakia (Minichova et al, ; Miťková et al, ). Furthermore , R. monacensis and R. helvetica are characterized as novel potential human pathogens in Europe (Jado et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Slovakia (Minichova et al, 2017;Miťková et al, 2015). Furthermore, R. monacensis and R. helvetica are characterized as novel potential human pathogens in Europe (Jado et al, 2007).…”
Section: And Inmentioning
confidence: 99%
“…Number [137,[141][142][143][144][145][146][147][148][149]. As far as we are aware, there are no published transmission experiments in laboratory animals for either species.…”
Section: Microorganismmentioning
confidence: 99%